'Are you equal to two German women?' 1941 (pg. 1) (1941)
1941 1939-1945 "'Are you equal to two German women?' 1941 (pg. 1)" [hfr0167], 1941 This article, reprinted from the 'Woman and Beauty' magazine in 1941, encourages women to join Ministry of Labour training schemes.